2013
DOI: 10.1021/cg3010618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structurally Similar Additives on Crystal Habit of Organic Molecular Crystals at Low Supersaturation

Abstract: Foreign molecules such as additives or impurities may influence crystal morphology to a significant extent by disrupting the growth mechanism and inhibiting the growth rate of certain crystal faces. The additives can be byproducts of a preceding reaction step, or they could be specially designed to obtain specific crystal morphologies for particular applications. Because of the specific chemical structure of structurally similar additives, they can incorporate or lock into the original lattice only in certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 42 publications
0
51
0
Order By: Relevance
“…Chernov ( 47 ), Cabrera ( 109 ), and Vermilyea ( 110 ) have extensively studied the influence of impurities on the development of surface dislocations on crystals and therefore crystal growth. Those studies set the groundwork for the development of a mechanistic framework ( 111 , 112 ) for the prediction of the influence of additives in crystal growth in the context of the infamous BCF model, mentioned earlier. It has been shown that additives posing similar structure with the molecules of the crystal can be used as effective crystal habit modifiers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chernov ( 47 ), Cabrera ( 109 ), and Vermilyea ( 110 ) have extensively studied the influence of impurities on the development of surface dislocations on crystals and therefore crystal growth. Those studies set the groundwork for the development of a mechanistic framework ( 111 , 112 ) for the prediction of the influence of additives in crystal growth in the context of the infamous BCF model, mentioned earlier. It has been shown that additives posing similar structure with the molecules of the crystal can be used as effective crystal habit modifiers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of external species such as structurally similar additives has been studied within the context of the mechanistic model [115]; however at present the ability to account for such effects has yet to be built into ADDICT.…”
Section: Kink Rate Model For Spiral Growthmentioning
confidence: 99%
“…Therefore, many attempts have been made to control those properties through the crystallization techniques. In the crystallization process, crystal size and shape are intimately related with nucleation and crystal growth kinetics . For example, final crystal size is strongly influenced by the population density of crystallizing body that is commonly induced by nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Growth kinetics of crystal faces is remarkably affected by structure and composition of chemicals surrounding a crystal due to their anisotropic nature. Therefore, crystal shape can be controlled by solvent or supersaturation control, and addition of tailor‐made additives, because the area of a crystal face is inversely proportional to growth rate of that face .…”
Section: Introductionmentioning
confidence: 99%